Determinants of financial inclusion gender gap in Ethiopia: Evidence from decomposition analysis - Shemelis Kebede Hundie; Daniel Tadesse Tulu (Cogent Business & Management, 2023)
In Ethiopia, the gender gap in financial inclusion is high, and the effect of socioeconomic variables on the gap is not well investigated. The main objective of this study is to investigate determinants of the financial inclusion gender gap in Ethiopia using the World Bank's Global Findex database from 2017. Different decomposition techniques were employed to examine the effect of socioeconomic characteristics of individuals on the financial inclusion gender gap. The finding shows a statistically significant gender gap in all indicators of financial inclusion under study in Ethiopia. More specifically, males are 6.3%, 7%, 9.8%, 8.4 %, and 5.8% more likely to have a formal account, formal saving, formal borrowing, emergency fund, and debit card ownership, respectively. The result from the Daymont and Andrisani approach reveals that differences in socioeconomic characteristics between males and females explain the gender gap in formal saving, formal account ownership, debit card ownership, and emergency fund, while the gap in formal borrowing is attributed to differences in returns to these characteristics. Besides, the observed gender gap in all indicators of financial inclusion is explained by gender disparity in commitment in financial markets. Age, income, education, employment, and mobile ownership are determinants of the gender gap in financial inclusion in Ethiopia. Being older, more educated, employed, and having mobile, and wealthier favor financial inclusion, with age, employment, and education having a greater effect. Gender mainstreaming in economic activities to increase income, employment opportunities, and education for females to bridge the gender gap in financial inclusion is important.
Keywords: 650; decomposition analysis; Ethiopia; financial inclusion; gender gap